SCHEDULING MAINTENANCE PROPOSAL FOR TURBINE MACHINES USING THE AGE REPLACEMENT METHOD AT BALAMBANO HYDROELECTRIC POWER PLANT PT. Vale Indonesia Tbk. - Malik, Rahmaniah; Rauf, Nurhayati; Alisyahbana, Takdir; Ahmad, Arfandi; Fole, Asrul (Center for Study and Journal Management FTI UMI, 2024)
PT. Vale Indonesia Tbk. is a company engaged in the mining industry, particularly in nickel processing (Ni). The company operates a power plant at Balambano Hydroelectric Power Plant (2x68.5 MW). The company's usual maintenance practice is limited to corrective maintenance, which involves replacing or repairing components only when they are damaged. The aim of this research is to determine the optimal replacement time for preventive maintenance on turbine machines in order to minimize downtime. The age replacement method is used to calculate the replacement interval for components based on their usage life. The research findings show that the mean time to failure (MTTF) of the wicket gate is 2217.824 hours or 92.41 days, which means that the component may experience failure again after operating for that MTTF duration. Therefore, the recommendation is to replace the component every 85 days of operation and perform inspections every 15 days.